Hydrogen Production Technologies - Assabumrungrat, Suttichai; Wongsakulphasatch, Suwimol; Kim-Lohsoontorn, Pattaraporn; Rodrigues, Alírio E. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Hydrogen has been an important feedstock for various industries, and its global market is already valued at hundreds of billions of dollars per year. It is also playing additional roles as a clean alternative energy carrier for power generation and as a crucial feedstock in the bioeconomy. This Special Issue "Hydrogen Production Technologies" highlights different thermochemical, electrochemical, and biological technologies such as high- and low-temperature electrolyzers, microchannel reactors, sorption-enhanced reactors, multi-tubular solar reactors, and anaerobic digestors. It also covers other aspects ranging from reactor design, hydrogen storage, and process analysis of different alternatives.